Late-onset systemic lupus erythematosus in Latin Americans: a distinct subgroup?. (July 2015) - Catoggio, L J; Soriano, E R; Imamura, P M; Wojdyla, D; Jacobelli, S; Massardo, L; Chacón Díaz, R; Guibert-Toledano, M; Alvarellos, A; Saurit, V; Manni, J A; Pascual-Ramos, V; et al.
Objective: To examine the characteristics of patients who developed late onset systemic lupus erythematosus (SLE) in the GLADEL (Grupo Latino Americano de Estudio del Lupus) cohort of patients with SLE. Methods: Patients with SLE of less than two years of disease duration, seen at 34 centers of nine Latin American countries, were included. Late-onset was defined as >50 years of age at time of first SLE-related symptom. Clinical and laboratory manifestations, activity index (SLEDAI), and damage index (SLICC/ACR- DI) were ascertained at time of entry and during the course (cumulative incidence). Features were compared between the two patient groups (<50 and ≥50) using descriptive statistics and hypothesis tests. Logistic regression was performed to examine the association of late-onset lupus, adjusting for other variables. Results: Of the 1480 patients included, 102 patients (6.9 %) had late-onset SLE, 87% of which were female. Patients with late-onset SLE had a shorter follow-up (3.6 vs. 4.4 years, p  < 0.002) and a longer time to diagnosis (10.1 vs. 5.8 months, p  < 0.001) compared to the younger onset group. Malar rash, photosensitivity, and renal involvement were less prevalent while interstitial lung disease, pleural effusions, and sicca symptoms were more frequent in the older age group ( p  > 0.05). In multivariable analysis, late onset was independently associated with higher odds of ocular (OR = 3.66, 95% CI = 2.15–6.23), pulmonary (OR = 2.04, 95% CI = 1.01–4.11), and cardiovascular (OR = 1.76, 95% CI = 1.04–2.98) involvement and lower odds of cutaneous involvement (OR = 0.41, 95% CI = 0.21–0.80), number of cumulative SLE criteria (OR = 0.79, 95% CI = 0.64–0.97), use of cyclophosphamide (OR = 0.47, 95% CI = 0.24–0.95), and anti-RNP antibodies (OR = 0.43, 95% CI = 0.20–0.91). A Cox regression model revealed a higher risk of dying in older onset than the younger-onset SLE (OR = 2.61, 95% CI = 1.2–5.6). Conclusion: Late-onset SLE in Latin Americans had a distinct disease expression compared to the younger-onset group. The disease seems to be mild with lower cumulative SLE criteria, reduced renal/mucocutaneous involvements, and less use of cyclophosphamide. Nevertheless, these patients have a higher risk of death and of ocular, pulmonary, and cardiovascular involvements.